Graduation after ten years of Ethiopia’s Productive Safety Net Programme: Surviving but still not thriving - Sabates-Wheeler, Rachel; Lind, Jeremy; Hoddinott, John F. (John Wiley & Sons, 2021)
Many social protection programmes aspire to graduate poor people out of poverty. While some successfully ensure food security and survival for the poorest, few have moved large numbers of people sustainably out of poverty and into productive livelihood opportunities.This article aims to understand better the challenges to sustainable graduation out of poverty, and why graduation has been so difficult to achieve in many social protection programmes.We define graduation and identify primary objectives related to food security and consumption and secondary objectives for asset accumulation. We then apply this thinking to the case of the Productive Safety Net Programme (PSNP) in Ethiopia, drawing on evaluation spanning the first 10 years of the programme.The programme has been successful on some fronts—such as saving lives, reducing distress sales and providing community‐level services—while on others, such as household asset building and livestock accumulation, it has failed to deliver. Given this, we ask why the programme has underperformed in building household assets, and further, why the PSNP programme proceeded to prematurely graduate so many households despite the lack of evidence on livelihood strengthening.It seems that the PSNP was unable to lift most households out of poverty, owing to lack of capacity to design and implement measures to raise incomes and to lack of opportunities to do so. Many households, however, were graduated out of PSNP, apparently because field staff had quotas to fulfil, whether or not the households had progressed out of poverty.The PSNP shows how a programme can succeed in its primary objective of alleviating deep poverty and preventing people from becoming destitute. But it also shows that to reach the more ambitious target of graduating households out of poverty, more funds and administrative capacity are needed to generate additional household economic activity. Investments in complementary rural services are needed as well.